Impact of Water Management on the Arsenic Content of Rice Grain and Cultivated Soil in an Arsenic Contaminated Area of Bangladesh (Journal of Environmental Science and Natural Resources, 2015)
A study was conducted in an arsenic (As) contaminated area of Faridpur, Bangladesh with a view to observe the effect of reduced irrigation on the As concentration of rice grain. Rice yield of BRRI dhan28 was found to be slightly higher in alternate wetting and drying (AWD) method than in continuous standing water (CSW) method of irrigation although not significant. The highest grain As conc. (0.65 mg/kg) was observed in the plots irrigated with ground water by CSW method. Significant reduction in grain As conc. was observed in AWD plots irrigated with contaminated ground water. Partial aeration of soil in AWD may have hindered the entrance of water As to rice roots. No significant reduction of soil As conc. was observed due to the application of AWD method. Reduction in grain As in AWD method implies that this technique can be devised as tool for mitigation of As in the As contaminated areas for irrigation of rice.DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22202 J. Environ. Sci. & Natural Resources, 7(2): 43-46 2014